2010
DOI: 10.1136/jmg.2009.074815
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma amplified sequence gene is associated with a novel short stature syndrome characterised by optic nerve atrophy and Pelger-Huet anomaly

Abstract: BackgroundHereditary short stature syndromes are clinically and genetically heterogeneous disorders and the cause have not been fully identified. Yakuts are a population isolated in Asia; they live in the far east of the Russian Federation and have a high prevalence of hereditary short stature syndrome including 3-M syndrome. A novel short stature syndrome in Yakuts is reported here, which is characterised by autosomal recessive inheritance, severe postnatal growth retardation, facial dysmorphism with senile f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
122
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 36 publications
4
122
0
1
Order By: Relevance
“…Fourth, the protein encoded by NBAS is thought to be involved in Golgi-to-endoplasmic reticulum transport [38]. SNPs in the NBAS gene may be connected with the pathogenesis of the short stature syndrome, optic atrophy and Pelger-Huët anomaly, which is characterized by a neutrophil whose nucleus is hyposegmented [39]. Overall, the results are suggestive of the hypothesis that some SNPs in genes related to the immune system may alter the LDL particle size.…”
Section: Discussionsupporting
confidence: 60%
“…Fourth, the protein encoded by NBAS is thought to be involved in Golgi-to-endoplasmic reticulum transport [38]. SNPs in the NBAS gene may be connected with the pathogenesis of the short stature syndrome, optic atrophy and Pelger-Huët anomaly, which is characterized by a neutrophil whose nucleus is hyposegmented [39]. Overall, the results are suggestive of the hypothesis that some SNPs in genes related to the immune system may alter the LDL particle size.…”
Section: Discussionsupporting
confidence: 60%
“…33 The Yakut population exhibits high rate of some Mendelian disorders, which are rare in other populations worldwide. High rates of spinocerebellar ataxia type 1 (SCA1), 32 myothonic dystrophy (DMPK), 26 oculopharyngeal muscular dystrophy (OPMD), 34 autosomal recessive methemoglobinemia (DIA1) 35 and two types of short stature disorders, 3-M (CUL7) and short stature with optic atrophy and Pelger-Huët anomaly (SOPH) syndrome (NBAS), 33,36 were previously found in Yakut population. We estimated the prevalence of DFNB1A associated with splice site IVS1+1G4A mutation in GJB2 gene as 16.2 in 100 000 in Yakut population, that is, higher compared with other common autosomal reccesive disorders found in Yakuts, such as autosomal recessive methemoglobinemia (14.9 in 100 000), 35 two types of short stature disorders, 3-M (10.0 in 100 000), 33 and SOPH syndromes (9.95 in 100 000).…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the prevalence of DFNB1A associated with splice site IVS1+1G4A mutation in GJB2 gene as 16.2 in 100 000 in Yakut population, that is, higher compared with other common autosomal reccesive disorders found in Yakuts, such as autosomal recessive methemoglobinemia (14.9 in 100 000), 35 two types of short stature disorders, 3-M (10.0 in 100 000), 33 and SOPH syndromes (9.95 in 100 000). 36 Thus, we suggested that autosomal recessive deafness 1A (DFNB1A) associated with homozygous mutation IVS1+1G4A in GJB2 gene is the most common autosomal recessive disease among Yakuts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 NBAS protein is expressed in epidermal skin cell, although it has not previously been implicated in chronic skin inflammatory diseases. 40 In contrast, genes at the 6q22.33, 10p14 and 15q24.3 locus are involved in immune dysregulation, which is a key pathogenic pathway in AD. The 6q22.33 and 10p14 loci include genes involved in adaptive immune responses, particularly in T cell differentiation.…”
Section: Discussionmentioning
confidence: 99%